2021
DOI: 10.3389/fnagi.2021.735524
|View full text |Cite|
|
Sign up to set email alerts
|

Uncovering Disease Mechanisms in a Novel Mouse Model Expressing Humanized APOEε4 and Trem2*R47H

Abstract: Late-onset Alzheimer’s disease (AD; LOAD) is the most common human neurodegenerative disease, however, the availability and efficacy of disease-modifying interventions is severely lacking. Despite exceptional efforts to understand disease progression via legacy amyloidogenic transgene mouse models, focus on disease translation with innovative mouse strains that better model the complexity of human AD is required to accelerate the development of future treatment modalities. LOAD within the human population is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 107 publications
0
72
0
Order By: Relevance
“…The R47H missense mutation in TREM2 directly implicates microglial biology in LOAD, and elucidating the underlying mechanisms depends on experimental models that recapitulate the human function. Results of previous studies of mice with the TREM2 R47H missense mutation introduced via CRISPR suggested that it acts as a near-complete loss of function, recapitulating phenotypes seen in Trem2 KO mice (Cheng-Hathaway et al, 2018;Kotredes et al, 2021). However, subsequent analyses of Trem2 expression and splicing in these models identified the unexpected generation of a cryptic splice site and subsequent loss of Trem2 expression due to the synonymous codon changes introduced as part of the CRISPR repair template (Xiang et al, 2018).…”
Section: The Trem2 R47h Nss Mutation Promotes Loss Of Oligodendrocyte...mentioning
confidence: 97%
“…The R47H missense mutation in TREM2 directly implicates microglial biology in LOAD, and elucidating the underlying mechanisms depends on experimental models that recapitulate the human function. Results of previous studies of mice with the TREM2 R47H missense mutation introduced via CRISPR suggested that it acts as a near-complete loss of function, recapitulating phenotypes seen in Trem2 KO mice (Cheng-Hathaway et al, 2018;Kotredes et al, 2021). However, subsequent analyses of Trem2 expression and splicing in these models identified the unexpected generation of a cryptic splice site and subsequent loss of Trem2 expression due to the synonymous codon changes introduced as part of the CRISPR repair template (Xiang et al, 2018).…”
Section: The Trem2 R47h Nss Mutation Promotes Loss Of Oligodendrocyte...mentioning
confidence: 97%
“…The copyright holder for this preprint this version posted February 12, 2022. ; https://doi.org/10.1101/2022.02.11.480032 doi: bioRxiv preprint homozygous for APOE4 and Trem2 R47H (termed LOAD1) [10]. Mice were aged to 24 months and data showed age but not genotype was the major factor driving changes in LOAD1 mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two centers, one from Indiana University (IU), The Jackson Laboratory (JAX), University of Pittsburg (Pitt) and Sage Bionetworks, and the other from University California Irvine (UCI) have focused on incorporating genetic risk factors into C57BL/6J (B6) mice and assaying human-relevant phenotypes. Initially, the IU/JAX/Pitt group created mice double homozygous for APOE4 and Trem2 R47H (termed LOAD1) [10]. Mice were aged to 24 months and data showed age but not genotype was the major factor driving changes in LOAD1 mice [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations